Ethnic Self-Esteem and Intergroup Attitudes Among the Estonian Majority and the non-Estonian Minority - Raudsepp, Maaris (Studies of Transition States and Societies, 2009)
The study was focused on the relationships between ethnic self-esteem and various indicators of intergroup attitudes  in a representative sample of adult population of Estonia (N=1142). Attitudinal variables that discriminated most between persons with high and low ethnic self-esteem were identiﬁed. Among Estonians  ethnic self-esteem was related to positive ingroup bias,  readiness for outgroup contact, perceived threat from the outgroup, attitudes to non-Estonian minority,  and attitudes toward minority integration. Among non-Estonians ethnic self-esteem was related to readiness for outgroup contact, ethnic sterotypes, and various attitudes towards minority integration. An attempt was made to reconstruct the system of intergroup attidues of prototypical persons with high and low ethnic self-esteem and to describe psychological implications of high and low ethnic self-esteem for members of majority and minority groups. Various theoretical models (social identity theory, integrated threat theory, social dominance theory) were used for interpretation of the results.